1999
DOI: 10.1093/emboj/18.19.5264
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of the ryanodine receptor type 3 (RyR3) impairs forms of synaptic plasticity and spatial learning

Abstract: Deletion of the ryanodine receptor type 3 (RyR3) results in specific changes in hippocampal synaptic plasticity, without affecting hippocampal morphology, basal synaptic transmission or presynaptic function. Robust long-term potentiation (LTP) induced by repeated, strong tetanization in the CA1 region and in the dentate gyrus was unaltered in hippocampal slices in vitro, whereas weak forms of plasticity generated by either a single weak tetanization or depotentiation of a robust LTP were impaired. These distin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
119
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(124 citation statements)
references
References 60 publications
(99 reference statements)
5
119
0
Order By: Relevance
“…A rota-rod test was, therefore, performed and an altered motor activity induced by substances at the doses used was excluded. The results of the rota-rod and hole board tests were of particular relevance since it has been observed that mice lacking type 1 inositol-1,4,5-trisphosphate receptor showed severe ataxia (Matsumoto et al, 1996) and motor discoordination (Ogura et al, 2001) and that deletion of the ryanodine receptor type 3 induced an increased speed of locomotion in the openfield (Balschun et al, 1999). Finally, it should be mentioned that thapsigargin is a widely used pharmacological tool to induce apoptosis.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A rota-rod test was, therefore, performed and an altered motor activity induced by substances at the doses used was excluded. The results of the rota-rod and hole board tests were of particular relevance since it has been observed that mice lacking type 1 inositol-1,4,5-trisphosphate receptor showed severe ataxia (Matsumoto et al, 1996) and motor discoordination (Ogura et al, 2001) and that deletion of the ryanodine receptor type 3 induced an increased speed of locomotion in the openfield (Balschun et al, 1999). Finally, it should be mentioned that thapsigargin is a widely used pharmacological tool to induce apoptosis.…”
Section: Discussionmentioning
confidence: 95%
“…The etiopathological role of RyRs has also been postulated at the central nervous system level. Deletion of RyR3 results in specific changes in intracellular processes underlying spatial learning and hippocampal synaptic plasticity (Balschun et al, 1999). RyR3 knockout mice have impairments of performance in the contextual fear conditioning test, passive avoidance test and Y-maze learning test (Kouzu et al, 2000) indicating the importance of RyR3 in the memory and learning processes.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, calpain activation, ryanodine receptors, and the release of Ca 2ϩ from intracellular stores are tied to aspects of AMPAr function. Calpain activation is required for LTP induction (Vanderklish et al, 1996), and recent studies of type 3 ryanodine receptors provide strong support for the involvement of intracellular Ca 2ϩ stores in calpain activation because deletion of this receptor impairs some forms of AMPAr-mediated synaptic plasticity, LTP, and spatial learning (Balschun et al, 1999;Shimuta et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In our experience, F2 generations preserve enough hybrid vigour to outperform both parental strains (Fig. 4) and very discrete mutation effects can be detected if sample sizes are large enough (Wolfer et al 1998a;Balschun et al 1999). While it appears acceptable to analyse mutations on a heterogeneous genetic background that is well defined and can be reproduced at any time, backcrossing to at least one, or preferably two, well-defined, commonly available inbred strains is mandatory for the long-term maintenance of a mutation.…”
Section: Figurementioning
confidence: 93%
“…Also labelled is a group of mice overexpressing L1 under the control of the GFAP promoter (L1) and showing slightly improved spatial flexibility (Wolfer et al 1998a). Groups not individually labelled include, among others, mice underexpressing âAPP in a truncated form (M uller et al 1994;Tremml et al 1998), a null-mutation of RasGRF (Brambilla et al 1997), mutations of CREB (Gass et al 1998), a null-mutation of RyR3 (Balschun et al 1999), and null-mutation of tPA (Huang et al 1996). For comparison, the subset also includes a group of non-mutant senile mice (S) and a group of C57BLÏ6 mice with chronically implanted intra-cerebroventricular canulas (CanB6).…”
Section: Genetic Background and Environmentmentioning
confidence: 99%